Comparison of p40 (ΔNp63) and p63 expression in prostate tissues – which one is the superior diagnostic marker for basal cells?. Issue 1 (13th May 2013) - Sailer, Verena; Stephan, Carsten; Wernert, Nicolas; Perner, Sven; Jung, Klaus; Dietel, Manfred; Kristiansen, Glen
<x xml:space="preserve">Abstract</x> Aims p63 is one of the standard markers for basal cells of the prostate gland. Recently, it has been suggested that the p63 isoform p40 might be more specific as a basal cell marker. In this study we compare the staining characteristics of p63 and p40 in normal and malignant prostate tissues. Methods and results A prostatectomy cohort (n = 640) in tissue microarray format was evaluated for p63 (clone 4A4) and for p40 (rabbit polyclonal) immunoreactivity in malignant and normal tissues. Immunoreactivity of basal and secretory cells was evaluated in a semiquantitative manner and compared case‐wise. In normal tissues, p40 showed highly similar immunoreactivity compared to p63. The staining patterns were absolutely identical in 88% of cases. Additional cytoplasmic p40 staining in tumour cells occurred in 59.6% of cancer cases. Differences were seen in nuclear staining of carcinomas: 1.4% of carcinomas were p63‐positive, whereas 0.6% were p40‐positive. Conclusions In most cases, p40 stains prostatic basal cells as reliably as p63, with only minor differences. Aberrant staining of tumour cells is seen more rarely than with p63 (clone 4A4), establishing its higher specificity. However, additional cytoplasmic immunoreactivity narrows its eligibility for antibody cocktails (e.g. with alpha‐methylacyl‐CoA racemase).